Deoxyribonucleic Acid Base Composition of Rothia dentocariosa as Determined by Thermal Denaturation - Hammond, B. F. (1970)
The moles per cent guanine plus cytosine (GC) of 10 filamentous strains of Rothia dentocariosa ranged from 65.4 to 69.7. Major differences were not observed in the base composition of a filamentous form (69.7 moles% GC) and its coccal variant (68.0 moles% GC).